2009
DOI: 10.1583/08-2515.1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Performance of Targeted Renal Therapy: The Be-RITe! Registry

Abstract: The Benephit system and TRT during coronary and endovascular procedures in patients at high risk for renal failure is simple to use and safe. With the infusion of intrarenal fenoldopam, the incidence of CIN was significantly lower than predicted by risk score calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…An attempt to minimize systemic hypotension by direct infusion of fenoldopam into the renal arteries has shown some promise in a proof-ofconcept trial 34 and an observational database. 35 …”
Section: Reversal Of Medullary Blood Flow Reductionmentioning
confidence: 99%
“…An attempt to minimize systemic hypotension by direct infusion of fenoldopam into the renal arteries has shown some promise in a proof-ofconcept trial 34 and an observational database. 35 …”
Section: Reversal Of Medullary Blood Flow Reductionmentioning
confidence: 99%
“…55,72 Recent findings derived from larger investigations have shown that fenoldopam can reduce the incidence of ICAinduced nephropathy, especially if administered directly into the renal arteries. [73][74][75] Direct administration into the renal vasculature has been shown to reduce the risk of systemic hypotension, possibly allowing higher doses of fenoldopam to reach the kidneys while avoiding systemic hypotension. Other agents, such as adenosine receptor antagonists and calcium channel antagonists, show mixed and inconsistent results in reducing the incidence of contrast-induced nephropathy.…”
mentioning
confidence: 99%
“…Targeted renal therapy with direct delivery of such agents to the kidneys via renal arteries during interventional radiological procedures has been reported to overcome such potential limitations [48]. Reduction in the incidence of CI-AKI has been reported with its use [49]. However, its efficacy and safety remains untested in a planned RCT and hence is not recommended [6].…”
Section: Prophylactic Measures Against Ci-akimentioning
confidence: 99%